All-Inkjet-Printed Low-Voltage Organic Thin-Film Transistors - Jiang, Chen (Apollo - University of Cambridge Repository, 2019)
This thesis presents the development of all-inkjet-printed low-voltage organic thin-film transistors. Organic thin-film transistors (OTFTs), taking advantage of low-temperature printability, mechanical flexibility, and multi-functionality, are promising for a wide range of emerging applications such as wearable electronics. Printed OTFTs provide great benefits in fabrication cost reduction, but they need a very high operating voltage and exhibit severe instability during storage and operation in ambient environment. In this study, all-inkjet-printed OTFTs with a low operating voltage of less than 3 V are demonstrated through reducing trap density in the fabricated devices. The transistors use 6,13-bis(triisopropylsilylethynyl)pentacene as the semiconductor, poly(4-vinylphenol) as the dielectric, silver as the electrodes, and CYTOP as the encapsulation. Several aspects of physical and chemical properties of polymer dielectrics are studied to achieve this goal, including cross-linking, wetting, and moisture affinity. Through the careful selection of device architecture and control of the inkjet-printing processes, the semiconductor-dielectric interface trap density of the fabricated OTFTs is significantly reduced. The applicability of this approach to different materials is also investigated and confirmed, including polyvinyl cinnamate as the dielectric, 2,7-dioctyl[1]benzothieno[3,2-b][1]benzothiophene as the semiconductor, and anisole as the solvent for semiconductor inks. Based on the investigation of different materials, the characteristics and parameters of all-inkjet-printed OTFTs are optimised, demonstrating an ultra-steep subthreshold of 60.2 mV/decade approaching the theoretical limit and a low operating voltage of 1 V. In order to explore their feasibility in real-world applications, the stability of all-inkjet-printed OTFTs is investigated and the factors of instability are analysed. Based on these findings, the stability of the fabricated device is improved, such that the threshold voltage shift is less than 0.1 V in ambient environment storage for 3 months and operation for 1 hour. The electrical characteristics of OTFTs in the subthreshold regime are studied for analogue circuit design. Based on the developed low-voltage stable transistors, an ultra-low-power (< 1 nW) high-gain (> 200 V/V) amplifier is presented and utilised to detect electrophysiological signals from the human body.
Keywords: Organic Thin-Film Transistors; Inkjet Printing; Low Operating Voltage; Low Power